2006
DOI: 10.1007/s00068-006-6051-z
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Films in Trauma and Orthopedic Surgery

Abstract: Resorbable materials have gained a considerable position in the daily routine of all surgical disciplines. Natural products like catgut and collagen have been used historically. Since the development of synthetical macromolecules more than 40 years ago, the range of indications for the use of such materials has widened significantly in our daily routine. Suture materials, mesh, tissue pads, clips, screws and anchors are in use. More recent developments in the field of orthopedic and trauma surgery include scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 78 publications
(84 reference statements)
0
10
0
1
Order By: Relevance
“…Bioresorbable dressings successfully address this shortcoming, since they do not need to be removed from the wound surface once they have fulfilled their role. Film dressings made of lactide-caprolactone copolymers such as Topkin Ò (Biomet, Europe) and Oprafol Ò (Lohmann & Rauscher, Germany) are currently available [4]. Biodegradation of these films occurs via hydrolysis of the copolymer into lactic acid and 6-hydroxycaproic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Bioresorbable dressings successfully address this shortcoming, since they do not need to be removed from the wound surface once they have fulfilled their role. Film dressings made of lactide-caprolactone copolymers such as Topkin Ò (Biomet, Europe) and Oprafol Ò (Lohmann & Rauscher, Germany) are currently available [4]. Biodegradation of these films occurs via hydrolysis of the copolymer into lactic acid and 6-hydroxycaproic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Wound healing currently not only aims to restore the milieu required for tissue regeneration but also to protect the wound from environmental threats and penetration of bacteria. Novel bioresorbable wound dressings successfully avoid clinical replacement since they do not need to be removed from the wound surface once they have fulfilled their role 1…”
mentioning
confidence: 99%
“…An ideal dressing should be able to be removed without inducing trauma during dressing change over healed areas in the wound bed. Resorbable materials are gaining considerable importance in all surgical disciplines and also for use as wound dressing (23). Physical and biological characterisation of the chitin membranes has shown that the membranes have ideal properties for a dressing and thus would aid in maintenance of a balanced moist wound environment to structural support for tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Counts/100 cm sq. Counts/g (23). Physical and biological characterisation of the chitin membranes has shown that the membranes have ideal properties for a dressing and thus would aid in maintenance of a balanced moist wound environment to structural support for tissue regeneration.…”
Section: Counts (Cfu)mentioning
confidence: 99%